SNAKES AND LADDERS GAME: AN ALTERNATIVE INSTRUCTIONAL STRATEGY TO ENHANCE THE LEARNERS’ GRAMMATICAL PROFICIENCY - Mahbub, Moh. Arif (Aksara, 2019)
This present study reports on the findings related to the use of the snake and ladder game as a strategy to enhance the learners’ grammatical proficiency in mastering simple future tense. The participants were 27 eleventh graders of SMK Asrama Pembina Masyarakat. A number of instruments used in this study. The developments of the students’ grammatical proficiency were collected through the two sets of pre-test and post-test. The data related to the students’ attitude toward grammatical problems and the implementation of snake and ladder game were collected through questionnaires. Observation was employed to record the students’ participation during the lesson. The findings revealed that the students’ grammatical proficiency significantly improved. There were 20 (74.07%) out of 27 students who passed the criterion of minimum completeness of 75. The average score of students showed 77.26. Through the distributed questionnaires, the findings also demonstrated the positive thoughts and attitudes related to the game they played during the lesson.  The students’ participation to the use of the snake and ladder game in teaching-learning activity in the classroom was also pleasing. It can be concluded that the application of this game can meet the all criteria of success of cycle. In other words, it can play positive role in developing the learners’ grammatical proficiency.